PELAKSANAAN DIPLOMASI DAN KERJASAMA LUAR NEGERI OLEH PEMERINTAH KOTA/KABUPATEN DI KARESIDENAN SURAKARTA - Kartika Giri, Herning Suryo & (Transformasi, 2017)
This research aims to explain how the implementation of local government cooperation withforeign countries or foreign NGO in 2012 until 2017 on around the region of Surakarta. Thedata of that kind cooperation was really hard to get in the newspaper and also by search it onthe internet, researchers want to collect all of international cooperation by local goverment onaround the region of Surakarta in 2012 until 2017. This is because, with the implementation oflocal government autonomy in Indonesian cities and region, now they can make cooperationwith foreign countries or foreign NGO but must still give priority on Indonesian nationalinterest. Researchers believe that altough we could not get it in internet, internationalcooperation between local government exist. By using the theory and concept of diplomacy,international cooperation and national interest, this research make use of qualitative methodwith primary data from the interview with local government staff in cooperation section and alsouse document-based research and explained by descriptive method. Through analysis weconcluded that local government on around the region of Surakarta already have severalinternational cooperation with foreign countries, cities or NGO in 2012 until 2017. But there arestill many obstacles in the implementation of MoU or LoI which already signed by both partiessuch as lack of coordination with national government, local goverment and also agencies whichdirectly involved with international cooperation, lack of capabilities in lobbying and negotiation,lack of english, and budgeting problems.Key words: Local Government, Diplomacy, International Cooperation, National Interest